2020
DOI: 10.1002/adma.202000992
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous PdAg Nanospheres for Stable Electrochemical CO2 Reduction to Formate

Abstract: Palladium is a promising material for electrochemical CO 2 reduction to formate with high Faradaic efficiency near the equilibrium potential. It unfortunately suffers from problematic operation stability due to the CO poisoning on surface. Here, we demonstrate that alloying is an effective strategy to alleviate this problem. Mesoporous PdAg nanospheres with uniform size and composition are prepared from the co-reduction of palladium and silver precursors in aqueous solution using dioctadecyldimethylammonium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(119 citation statements)
references
References 37 publications
6
113
0
Order By: Relevance
“…Although such a strategy has been applied as a general design principle of Pd alloys for electrocatalytic oxygen reduction reaction and alcohol oxidation reaction, [34][35][36][37] the alloying effect is much less explored and appreciated for CO 2 RR until very recently. [38][39][40][41] In this contribution, we investigate the great potential of 1D alloy nanowires of Pd and Ag in CO 2 RR electrocatalysis. Ag is selected as the second metal in the alloy for its electron-rich state and weak CO binding strength.…”
Section: Doi: 101002/adma202005821mentioning
confidence: 99%
“…Although such a strategy has been applied as a general design principle of Pd alloys for electrocatalytic oxygen reduction reaction and alcohol oxidation reaction, [34][35][36][37] the alloying effect is much less explored and appreciated for CO 2 RR until very recently. [38][39][40][41] In this contribution, we investigate the great potential of 1D alloy nanowires of Pd and Ag in CO 2 RR electrocatalysis. Ag is selected as the second metal in the alloy for its electron-rich state and weak CO binding strength.…”
Section: Doi: 101002/adma202005821mentioning
confidence: 99%
“…In addition to water splitting, electrocatalytic reactions are also widely exploited in other realms. For example, CO 2 reduction reaction (CO 2 RR) can be exploited to produce carbon monoxide, [ 290 ] ethylene, [ 291 ] methane, [ 292 ] formate, [ 293–295 ] syngas, [ 296 ] or even gasoline fuel. [ 297 ] Ammonia, an essential chemical for both agriculture and industry applications, can be synthesized by nitrogen reduction reaction (NRR) under room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the performance of the electrocatalytic CO2 reduction reaction (CO2RR) is compromised during electrolysis [2,[50][51][52]. This is often attributed to catalyst deactivation by the adsorption of reaction intermediates.…”
Section: Catalyst Poisoningmentioning
confidence: 99%
“…Thus, density-functional theory (DFT) calculations have often revealed higher binding energy between the poisoned catalysts and the implicated species. For instance, Pd metal is known to bind strongly to CO and is more likely to be poisoned and undergo activity degradation in a short duration of time due to the reduction of CO2 to CO [50][51][52]. The strong CO adsorption arises from an increase in 2π* back donation interaction (i.e., electron donation from the d orbitals of the metal substrate to the 2π* orbital of CO) as the formed bonding resonances are filled at a more negative potential [57].…”
Section: Catalyst Poisoningmentioning
confidence: 99%
See 1 more Smart Citation